Digital Marketing Transformation Optimization: Building Superior Brand Awareness for Hydroponic Products - D. Iwan Riswandi; Denpharanto Agung Krisprimandoyo; Siska Armawati Sufa; Aulia Afniar. R; Athok Murtadlo (Sinergi : Jurnal Ilmiah Ilmu Manajemen, 2024)
This study examines the process of enhancing digital marketing transformation in order to establish a stronger brand awareness for hydroponic products. The objective of this study is to enhance the efficacy and productivity of digital media marketing through the examination of digital marketing strategies employed by hydroponic companies and the creation of novel approaches. The literature review encompasses the subjects of digital marketing, brand recognition, and hydroponics. The study methodology employed is qualitative, utilising data obtained from various sources such as articles, newspapers, journals, books, online articles, library data, and other relevant materials. The findings indicate that strategically enhancing digital marketing transformation, namely through popular social media platforms like Facebook, Instagram, TikTok, and YouTube, can effectively boost the visibility and recognition of hydroponic products. MSMEs and educational institutions have the ability to significantly broaden their promotional endeavours and enhance the visibility of hydroponic products. The study's findings suggest that optimising digital marketing transformation can be a very effective approach to enhance brand awareness for hydroponic products. This is particularly true when utilising major social media sites like Facebook, Instagram, TikTok, and YouTube. MSMEs and educational institutions could leverage this digital marketing change to broaden the promotional reach and enhance the visibility of the products.